Perceptions of people with hiv/aids towards stigma in performing oral health services - Pramono, Berlian Huwaida; Mujayanto, Rochman (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: HIV/AIDS sufferers have many negative influences in their lives, such as experiencing problems of stigma and discrimination in their lives. Stigma is bad prejudice, and discrimination is unfair treatment of fellow humans. Prejudice and discriminatory behavior on the part of dental health care providers constitutes a significant barrier to normal dental health care for people living with HIV/AIDS. This study aims to determine the perceptions of people with HIV/AIDS regarding stigma in providing dental and oral health services. Method: This research method is a descriptive observational type which consists of two variables, namely the independent variable perception and the dependent variable stigma. The population of this study was carried out on HIV/AIDS sufferers at the Islamic Dental and Oral Hospital Semarang who had received dental and oral health services with 70 respondents as research subjects. Respondents filled out the questionnaire in a structured manner. In addition to sociodemographic variables, perceptions of public and private dental services and professionals were evaluated, as well as perceived stigma related to HIV/AIDS, via a Likert-type scale. Statistical evaluation using descriptive statistics to see the mean, median and mode values. Result: The results of the research show that people with HIV/AIDS have a good perception of stigma so that people with HIV/AIDS when providing dental and oral health services feel very comfortable because there is no stigma and discrimination they experience. Conclusion: It can be concluded that Perceptions of people living with HIV/AIDS regarding stigma in providing dental and oral health services, respondents have good perceptions regarding stigma and discrimination in health services.